Assessment of medical criteria for referring neurological patients to physical therapy treatment (Fisioterapia e Pesquisa, 2006)
The aim of the present study was to investigate the criteria used by neurologists to refer patients to physical therapy treatment. All (44) neurologists from a university hospital were contacted. Thirty physicians answered a questionnaire composed by 12 multiple choice questions and four open ones, in view of assessing both their referral criteria and theirpersonal perception of the effectiveness of physical therapy treatment. The Spearman test was used to assess relations between such perception and physicians' time of professional experience. Most physicians (70%) had graduated for over 3 years. Though almost all (97%) reported referring most patients to physical therapy, only 48.3% said they were sure about this treatment effectiveness. And, the longer their time of professional experience, the greater their belief in physical therapy effectiveness (r=0.8; p<0.02). However, most of the interviewed (53%) reported not being aware of scientific evidence on physical therapy treatments and 60% reported they had never read any scientific studies on it. Results suggest that neurologists' referral is grounded rather on their clinical experience and reinforce the need for physical therapists to disseminate scientific evidence so as to subsidize neurological patients referral.